SUSTAINABLE DEVELOPMENT OF RURAL AREAS - CASE STUDIES VOJVODINA - SERBIA - Forcan, Dejana (International Journal of Economic Practice and Policy, 2017)
One of the most important strategic aims of Serbian economic development is supporting of the villages sustainable development through rural economy diversification where rural tourism development has an important place. In spite of this model of tourism importance recognition as a possible way of rural areas development, Serbia is in an opening phase of. Although there are several positive examples, it is significant that recent projects haven’t been established according to national and European development programs, but according to private initiatives of individuals and groups. Rural tourism is an important component of integrated and sustainable development and revitalization of villages, as well an an important factor in encouraging the development of local agricultural and non-farmer activities in rural areas and villages, and also a special incentive to employment. This work highlights the importance of rural tourism in the function of the revitalization of the village, focusing on the challenges of the environment and the possible directions of development in the context of creating a recognizable tourist product and brand of rural tourism in Vojvodina.